Investigating associations between nutritional status, body composition, eating behavior, and somatotype with physical fitness among urban adult women - Hanisah, Sarah Firjani; Purwaningtyas, Desiani Rizki (World Nutrition Journal, 2025)
Background: Reduced physical fitness increases the risk of non-communicable diseases (NCDs) such as obesity, hypertension, and type 2 diabetes. In urban Indonesia, this is particularly concerning, with over 33.9% of adult urban women classified as obese. Although nutritional status, body composition, eating behavior, and somatotype may affect fitness, few studies have explored these relationships within this population. Objectives: This study aims to explore the associations between these factors and physical fitness among urban adult women.